Adaptive Impedance Control Based on CoM for Hexapod Robot Walking on the Bottom of Ocean - Addie Irawan, Hashim; Alam, Md. Moktadir (2015)
This paper presents a proposed adaptive impedance control that derived based on Center of Mass (CoM) of the hexapod robot for walking on the bottom of water or seabed. The study has been carried out by modeling the buoyancy force following the restoration force to a chieve the drowning level according to the Archimedes’ principle. The restoration force need to be positive in order to ensure robot locomotion is not affected by buoyancy factor. As for this force control solution, impedance control has been derived based on the total of for ce of foot placement to consider CoM of the robot during walking period. This derived impedance control is design for the real-time based 4 degree of freedom (DoF) leg configuration of hexapod robot model. The scope of analysis is focus on walking on the varied stiffness of undersea bottom soil with tripod walking pattern. The verification is done on the vertical foot motion of the leg and the body mass coordination movement during walking period. The results shows that proposed impedance control able to control the force restoration factor by making vertical force on each foot bigger enough (sufficient foot placement) if compare to the buoyancy force of the ocean, thus performing stable tripod walking on the seabed with uncertain stiffness.